Effective Factors in Adopting Electronic Books E books by Students in Electronic Era - Nazari, Malihe; Abdekhoda, Mohammedhiwa (DESIDOC Journal of Library & Information Technology, 2021)
The current study was conducted with the aim of identifying effective factors in students’ utilise of e-books by combining the Expectancy Disconfirmation Theory and Technology Acceptance Model. The current study is a descriptive-analytical study using confirmatory factor analysis. The study population included students of Tabriz University of Medical Sciences. A randomised sampling method was used from the available population, including 140 participants selected as the study population, and the research instrument was a questionnaire constructed based on the Expectance Disconfirmation Theory (EDT) and Technology Acceptance Model (TAM). The findings indicate that factors of the TAM, that is, perceived usefulness (PU) (=β0.64) and perceived ease of use (PEOU) (=β 0.42) have a positive and significant effect on student’s use of e-books. Other findings indicate that the suggested model is able to depict over 47 per cent of effective factors in using e-books by students. Thus, the combination of TAM and EDT models is appropriate for depicting students’ behavior in using e-book. The results of this study clearly identified the effective factors in student’s use of e-books, including PU, PEOU, confirmation, and user satisfaction. The results of current study can be beneficial for the implementation of e-books in libraries and educational settings.